2002
DOI: 10.1055/s-2002-35732
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Ulnar Flow is Helpful in Predicting Ischemia after Radial Artery Harvest

Abstract: Combined use of ulnar flow measurement with the Allen test appears to increase the sensitivity of the Allen test. Neither test, however, is sufficient for a group of patients with large interosseous collaterals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 9 publications
0
12
0
2
Order By: Relevance
“…Abu-Omar et al [50] reported that 88% of patients with a positive Allen test had no forearm arterial occlusive disease according to Doppler ultrasonography, thus the RA could be harvested without any ischemic complications in the hand. A rare case of severe hand ischemia in a patient despite a negative Allen test result was also reported [13,[59][60][61][62]. A well-developed collateral circulation [63], a superficial dorsal branch of the RA, or a median artery [64] can provoke such a misleading result.…”
Section: Preoperative Exclusion Criteria For Ra Harvestingmentioning
confidence: 99%
See 1 more Smart Citation
“…Abu-Omar et al [50] reported that 88% of patients with a positive Allen test had no forearm arterial occlusive disease according to Doppler ultrasonography, thus the RA could be harvested without any ischemic complications in the hand. A rare case of severe hand ischemia in a patient despite a negative Allen test result was also reported [13,[59][60][61][62]. A well-developed collateral circulation [63], a superficial dorsal branch of the RA, or a median artery [64] can provoke such a misleading result.…”
Section: Preoperative Exclusion Criteria For Ra Harvestingmentioning
confidence: 99%
“…Motor impairments are usually early findings of little clinical importance [136,141]. Finally, although severe hand ischemia after RA harvest is rare [13,[59][60][61], patients suffering from forearm arterial occlusive disease are prone to this complication [110]. After RA harvesting, the UA dilation compensates for the loss of the RA [110].…”
Section: Complications After Ra Harvestingmentioning
confidence: 99%
“…False normal rates range from 3% to 45.5%, and false abnormal results might be as high as 73%, depending on technique (15)(16)(17). Some authors have suggested that the AT should be replaced by more objective and reliable tests such as Doppler ultrasound and plethysmography before the RA is cannulated or harvested The Allen's Test in Transradial Angiography for coronary bypass surgery (11,(17)(18)(19)(20). Conversely, other authors have suggested that assessment of the ulnar collateral circulation is unnecessary, owing to the absence of complications in their series (which included patients with abnormal AT) and the fact that complications often occurred in patients with a normal AT (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…Manabe y cols. 5,6 arriban a interesantes datos en cuanto a la toma de decisión preoperatoria a fin de pronosticar potenciales alteraciones en la perfusión de la mano y apuntan a la actividad laboral y recreativa que desarrollará el paciente luego de la cirugía. Los autores concluyen en que los diámetros <1,4 mm/m 2 de la arteria cubital y los flujos <60 ml/min/m 2 , medidos en la muñeca, son indicadores de riesgo de intolerancia durante el ejercicio.…”
Section: Higginsunclassified
“…5,6 comunican un 12,5% de pacientes con síntomas de isquemia moderada en esta situación; en nuestra serie, fue del 4,8% correspondiente a dos pacientes aislados cuyos síntomas fueron leves y ocasionales.…”
Section: Tabla Comparación Estadística De Variables En Ambas Manosunclassified